Choosing IoT‐connectivity? A guiding methodology based on functional characteristics and economic considerations. Issue 5 (19th April 2018) - Vannieuwenborg, Frederic; Verbrugge, Sofie; Colle, Didier
Abstract: Along with the growing market of Internet of Things (IoT), the set of IoT‐connectivity networks is also continuously expanding. Large‐scale deployments of the new low‐power wide‐area networks and announcements of new technologies prove this trend. Although these new technologies take care of some key IoT‐challenges, such as communication cost and power consumption, careful consideration of the IoT‐connectivity is still required since there is no one‐size‐fits‐all solution. Typical comparisons of IoT‐connectivity networks are based on technical characteristics but remain unpractical when it comes down to comparing functional characteristics. Questions on public network accessibility, ability for private network deployments, and cost considerations related to IoT‐connectivity networks often remain unanswered. In this work, a 2‐step methodology is proposed to guide IoT‐developers in choosing an appropriate connectivity network. First, a questionnaire walkthrough eliminates IoT‐connectivity networks based on mismatches between their functional characteristics and the functional requirements of the IoT‐applications. In a second step, an evaluation of the main cost components related to IoT‐connectivity indicates the most economical solution. As an illustration, we present 2 case studies: (1) deploying smart shipping containers in the port of Antwerp and (2) installing shop'n go parking spaces, which detect vehicle presence via a sensor. Abstract : New IoT‐connectivity networks tackle some key IoT‐challenges such as communication cost and power consumption. But careful consideration of the network technology is required since there is no one‐size‐fits‐all solution. In this work a two‐step methodology is proposed to choose an appropriate connectivity network from both a technical and economic perspective. First, a questionnaire eliminates different options based on mismatches between network characteristics and IoT‐application requirements. Next, an evaluation of the cost components related to IoT‐connectivity indicates the most economical solution.